2012
DOI: 10.4103/0975-1483.104375
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphism in Amlodipine Induced Gingival Hyperplasia: A Case Report

Abstract: The management of cardiovascular disorders poses a dilemma for the medical fraternity. Calcium channel blockers are one of the most commonly used drugs for the management of this disorder, and it is also a well known fact that they are one of the most common group of drugs responsible for causing gingival over growth as one of their adverse effects. Amlodipine is a new generation hypertensive, which has found wide acceptance and usage due to its duration of action. Even with all its benefits as a potent hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
1
10
0
Order By: Relevance
“…Management of gingival enlargement secondary to amlodipine use involves phase I periodontal therapy, drug substitution, follow‐up and gingivectomy in indicated regions. Several case reports have shown that patients treated by the above method responded well . In our experience, the first and third patients responded well to drug substitution and oral prophylaxis.…”
Section: Case Descriptionsupporting
confidence: 55%
See 1 more Smart Citation
“…Management of gingival enlargement secondary to amlodipine use involves phase I periodontal therapy, drug substitution, follow‐up and gingivectomy in indicated regions. Several case reports have shown that patients treated by the above method responded well . In our experience, the first and third patients responded well to drug substitution and oral prophylaxis.…”
Section: Case Descriptionsupporting
confidence: 55%
“…Gingival enlargement associated with this drug was first reported by Ellis et al . Previous studies have implicated the role of multidrug resistance 1 (MDR1) gene in such cases of amlodipine‐induced gingival enlargement . This article describes the association of MDR1 gene polymorphism in three patients with gingival enlargement secondary to amlodipine intake and their response to simple drug substitution and periodontal therapy.…”
Section: What Is Known and Objectivementioning
confidence: 87%
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Charles et al . in 2012[13] reported a case of amlodipine-induced gingival hyperplasia associated with MDR1 3435C/T gene polymorphism. This gene polymorphism was suggested to alter the inflammatory response of the gingival tissues to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The pharmacologic effect of each of these drugs is different but all of them seem to act similarly on secondary target tissue, i.e., the gingival connective tissue, causing common clinical histopathological findings. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%